Changes in protected area management effectiveness over time: A global analysis. (November 2015) - Geldmann, Jonas; Coad, Lauren; Barnes, Megan; Craigie, Ian D.; Hockings, Marc; Knights, Kathryn; Leverington, Fiona; Cuadros, Ivon C.; Zamora, Camilo; Woodley, Stephen; Burgess, Neil D.
Abstract: Protected area coverage has reached over 15% of the global land area. However, the quality of management of the vast majority of reserves remains unknown, and many are suspected to be "paper parks". Moreover, the degree to which management can be enhanced through targeted conservation projects remains broadly speculative. Proven links between improved reserve management and the delivery of conservation outcomes are even more elusive. In this paper we present results on how management effectiveness scores change in protected areas receiving conservation investment, using a globally expanded database of protected area management effectiveness, focusing on the "management effectiveness tracking tool" (METT). Of 1934 protected areas with METT data, 722 sites have at least two assessments. Mean METT scores increased in 69.5% of sites while 25.1% experienced decreases and 5.4% experienced no change over project periods (median 4 years). Low initial METT scores and longer implementation time were both found to positively correlate with larger increases in management effectiveness. Performance metrics related to planning and context as well as monitoring and enforcement systems increased the most while protected area outcomes showed least improvement. Using a general linear mixed model we tested the correlation between change in METT scores and matrices of 1) landscape and protected area properties (i.e. topography and size), 2) human threats (i.e. road and human population density), and 3) socio-economics (i.e. infant mortality rate). Protected areas under greater threat and larger protected areas showed greatest improvements in METT. Our results suggest that when funding and resources are targeted at protected areas under greater threat they have a greater impact, potentially including slowing the loss of biodiversity. Highlights: We collected the largest global database of change in management effectiveness. Management effectiveness, on average improved in 722 protected areas from 74 countries. Management elements related to planning increased the most followed by enforcement. Measures on biological condition assessments did not improve over time. Increased human population density predicted increases in management effectiveness.